Associations among Serum Glucose and Insulin with Pro-Inflammatory and Anti-Inflammatory Cytokine Levels in Bangladeshi Newly Diagnosed Type 2 Diabetes Mellitus Patients (Bangladesh Journal of Medical Biochemistry, 2025)
Literature review indicated that very limited studies on associations (correlations) among serum glucose and insulin with pro-inflammatory (IL-1, IL-6, TNF-α) and anti-inflammatory cytokine (IL-4, IL-10, Il-13) levels in newly diagnosed Bangladeshi patients with Type 2 diabetes mellitus (T2DM) have been reported. We therefore investigated those associations in newly diagnosed Bangladeshi T2DM patients and the findings are reported in the present article. Suspected patients with T2DM had undergone oral glucose tolerance test (OGTT) after overnight fasting. Blood samples were collected from patients at ‘0’ min (Fasting) and at 2 hrs (120 min) after OGTT. Newly OGTT positive 36 adult patients (Male: 15, Female: 21, Age: 35-65 years) and 30 normal healthy subjects (Male: 12, Female: 18; Age range: 32-67 years) were investigated in parallel as controls. Patients having any kind of metabolic diseases and taking hypoglycemic drug therapy were excluded from the study. Serum levels of pro–inflammatory (IL-1, IL-6, TNF-α) and anti-inflammatory cytokines (IL-4, IL-10, Il-13) were determined by enzyme immunoassay (EIA) methods using research kits obtained from reputed companies at Medical Research Unit (MRU), MCW&H building, MHWT, Dhaka, Bangladesh. The associations among FBG and fasting pro-inflammatory cytokines (F-IL-1, F-IL-6, F-TNF-α) revealed that F-IL-1 vs F-TNF-α (r=0.346, p=0.039) and F-IL-1 vs F-IL-6 (r=0.394, p=0.018) were significant (p0.05). The associations of pro-inflammatory cytokines at 2 hrs of OGTT (IL-1, 2hr, IL-6, 2hr, TNF-α, 2hr) in T2DM patients revealed that IL-1, 2hr vs TNF-α, 2hr was significant (r=0.454, p=0.005). Blood glucose 2 hours (BG2Hr) level did not show significant correlations with any of the pro-inflammatory cytokines (p>0.05). Associations of F-insulin with any of the fasting pro-inflammatory cytokines were not significant (p>0.05). However, the associations of F-IL-1 vs F-IL-6 (r=0.394, p=0.018) and F-IL-1 vs F-TNF-α (r=0.346, p=0.039) were significant (p0.05). However, IL-1, 2hr vs TNFα, 2hr was associated significantly (r=0.454, p=0.005). FBG did not show any significant associations with anti-inflammatory cytokines (p>0.05). BG2Hr also did not show any significant associations with the anti inflammatory cytokines (p>0.05). However, the association between IL-4, 2Hr vs IL-13, 2hr was significant (r=0.380, p=0.022). F-Insulin and any of the other comparisons did not show any significant associations (p>0.05). Also, Insulin 2Hr did not show any significant associations (p>0.05). However, the association between IL-4, 2Hr vs F-IL-13, 2Hr was found to be significant (p=0.022). These significant and non-significant associations obtained among FBG, BG2Hr, F-Insulin and insulin 2hr with pro-inflammatory (IL-1, IL-6, TNF-α) and anti-inflammatory (IL-4, IL-10, IL-13) cytokines were discussed relevant to pathogenesis of T2DM in Bangladeshi patients.Bangladesh J Med Biochem 2020; 13(2): 47-62